PROFIL KETERAMPILAN GERAK DASAR LOKOMOTOR SISWA DI SEKOLAH DASAR NEGERI 23 LUBUK ALUNG KABUPATEN PADANG PARIAMAN - Syahrani, Luzy; Andli Marta, Ibnu; Bakhtiar, Syahrial; Oktavani, Lucy (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the locomotor skills profile of students at State Elementary School 23 Lubuk Alung, Padang Pariaman Regency. This research is expected to provide a clear overview of students' locomotor skill conditions and serve as a basis for improving physical education. This research employs a descriptive method with a quantitative approach. The sample consists of 36 students selected using a purposive sampling technique. The instrument utilized is the Test of Gross Motor Development-2 (TGMD-2) subtest, focusing on locomotor skills. Data were analyzed using percentage descriptive statistical techniques with a 5-point scale application to determine students' ability classification. The results indicate that out of 36 students: (1) 3 students (8.33%) are classified as "Excellent"; (2) 8 students (22.22%) "Good"; (3) 13 students (36.11%) "Fair"; (4) 10 students (27.78%) "Poor"; and (5) 2 students (5.56%) "Very Poor". The average locomotor score is 30 points with a standard deviation of 5.02 (Fair category). These findings indicate the need for enhanced, structured physical education and full teacher support.